Rediscover of the Iranian endemic alpine Arenaria bulica after 139 years and note of the related species (Caryophyllaceae) - Pahlevani, Amirhossein; Falatoury, Atiye Nejad (Phytotaxa, 2024)
The Zagros Mountain range is one of the biodiversity centers with the highest percent of endemic species in Iran. There are several peaks with more than 4000 m high in Zagros hosting many rare alpine species. Arenaria is one of the morphological complicated genera with a large number of species and endemism in SW-Asia with an high species concentration in Turkey and Iran. By recollecting the rare and endemic species of Arenaria bulica from locus classicus after 139 years and examining the herbarium specimens, it was found that the two species, A. minutissima and A. semiromica can be considered as its synonyms. A detailed description, original photos, habitat, distribution map, phytogeography, conservation status, seed micromorphology and growth form have been provided and discussed.